The Effect of Picture Media on The Mastering Arabic Vocabulary in The 2nd Grade of Islamic Primary School Manarul Ilmi Al-Fajr Tanjungpinang - Eko Purnama; Fajar Tresna Utama; Ahmad Jalili; Aidillah Suja (PT. Berkah Smart Academica, 2024)
This study aims to explore the effect of using picture media on Arabic vocabulary acquisition among 2nd grade students at Islamic Primary School Manarul Ilmi Al-Fajr Tanjungpinang. Using a quantitative approach with a pseudo-experimental design, this study involved students and teachers as research subjects. Data were collected through observation and tests, then analyzed using descriptive statistical analysis and t-test using SPSS software version 25. The results showed that picture media significantly improved students' mastery of Arabic vocabulary. Students' post-test scores showed a significant increase compared to the pre-test, indicating that the pictures helped in facilitating a better understanding of the new vocabulary. Picture media not only increases students' motivation and engagement, but also enriches the learning experience by providing relevant visual context. These findings emphasize the importance of using appropriate learning media in language teaching to support better learning outcomes.